Effectiveness of Financing in Supporting MSME Development at PT Pegadaian UPS Kwanyar - Firdaus, Rifqi; Makhtum, Ahmad (Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: This research aims to analyze the effectiveness of financing in supporting MSME development at PT Pegadaian UPS Kwanyar. Research Methods: This research uses a descriptive case study approach to describe the efficiency and challenges of KUR Syariah at PT Pegadaian UPS Kwanyar. Data was collected through direct observation and interviews with the company and the MSME players. The data was then analyzed qualitatively using descriptive analysis. Results: The results reveal that the KUR Syariah program at PT Pegadaian UPS Kwanyar effectively supports MSME capital by implementing strict procedures such as timeliness, accuracy of amount, accuracy of target, and accuracy of credit. MSMEs that use KUR Syariah report increased income and productivity, although they still face challenges such as product limitations, low user interest, a complicated application process, and a lack of direct promotion. Conclusion: Improvements in the application process and promotion are needed to increase the utilization of KUR Syariah by MSMEs in Bangkalan City.